Bem-estar no trabalho: impacto das políticas de gestão de pessoas e da confiança organizacional - Poli, Bânia Vieira dos Santos (2013)
Well-being at work is an issue that has been highlighted in national and international literature, especially from the viewpoint of positive psychology. Accordingly, researchers have tried to investigate factors that favor the experience of well-being at work. Thus, this study aimed to investigate the impact of policies on people management and organizational trust on well-being at work. The study included 212 workers formally linked to different organizations (public = 16.5%), mostly female (71.9%), aged 18-59 years (M = 28, SD = 8.66) The level of education is predominantly incomplete third degree (34%). Instruments used were valid and reliable for each construct for data collection, with Cronbach\'s alpha exceeding 0.70. The reliability of the scales for the study sample showed coefficients above 0.70. We calculated standard multiple regression analyzes, using as dependent variables the factors of well-being at work (positive affect, negative affect, and achievement) and independent variables, perceived political people management (recruitment and selection, training and development, involvement , working conditions, rewards and performance appraisal) and organizational trust (ethical components, organizational competence and opportunism). The results showed that the significant predictors of positive affect were political people management (PGP) on the involvement / training and confidence in the ethics of the organization (model R2 = .39). The explanatory variables of negative affect and achievement were PGP involvement / training and working conditions, together accounted for 29% of variance explained. PGP involvement / training has positive relationship with achievement and negatively with negative affect, ie, the perception of these policies provides an opportunity to reach potential and achievement of individual targets and the lower their perception greater the experience of negative affect. Identified, therefore, the importance of the unique contribution of practices of recognition, participation and communication aimed at creating an emotional bond and psychological identification with the work of the people - political involvement. On the other hand, the PGP relating to working conditions showed exciting results by relate negatively with achievement and positive with negative affect. The conclusion of study indicates the importance of policies for managing people and organizational trust in promoting well-being at work also suggests new studies covering other samples in order to verify the relationships found.